2018
DOI: 10.1007/s40544-018-0208-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of EHD grease lubrication in finite line contacts

Abstract: Abstract:The objective of this study was to investigate the grease-lubricated film-forming mechanisms in the finite line contact and to improve the grease-lubricated finite line contact's film-forming capacity. An elastohydrodynamic lubrication (EHL) test rig with two interferometry microscopes, which could simultaneously monitor two different contact locations in the finite line contact, was constructed in order to study the influences of the grease thickener formulation on the film thickness and lubrication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
(16 reference statements)
1
4
0
Order By: Relevance
“…4(b), Fig. 7(b), and previous observations [8,[22][23][24]51]. The breakdown of lumps from their intact state to small particles contributes to the transition from distorted contact to normal contact, as shown in Fig.…”
Section: Formation Of Thick Filmsupporting
confidence: 75%
“…4(b), Fig. 7(b), and previous observations [8,[22][23][24]51]. The breakdown of lumps from their intact state to small particles contributes to the transition from distorted contact to normal contact, as shown in Fig.…”
Section: Formation Of Thick Filmsupporting
confidence: 75%
“…The results showed that in the oil starvation condition, lubricant molecules rearrange to form an ordered layer and a thicker critical film. Wang et al [107] by using the relative light intensity method [76], obtained the thickness maps of the grease-lubricated films from the interferometer images captured by the two microscopes. Their test results revealed that the grease thickener's formulation had remarkable effects on film formation and the perturbation of film thickness.…”
Section: Oil-based Lubricationmentioning
confidence: 99%
“…The dependence of the structure and properties of the polymer greases on the concentration of lithium stearate was established. Also, the scientific works of the authors [9][10][11][12] are devoted to various aspects of the use of greases in technical applications. At the same time, the analysis of studies has shown that little attention has been paid to the study of the deformation properties of greases under various conditions of tribological contact.…”
Section: Literatuter Reviewmentioning
confidence: 99%